BioNimbuZ: a federated cloud platform for bioinformatics applications. (2017) - AraÁºjo, Aletéia; Rosa, Michel; Moura, Breno; Vergara, Guilherme; Holanda, Maristela; Walter, Maria Emília
Challenges in bioinformatics include tools to treat large-scale processing, mainly due to the large volumes of data generated by high-throughput sequencing machines. However, many of these tools are not user friendly, and do not distribute their workloads properly. In federated cloud environments, even though services and resources are shared and available online, the processes of a workflow execution are almost entirely unautomated, and the majority of these processes do not efficiently balance their workloads. This paper presents the federated cloud platform called, BioNimbuZ - a hybrid platform designed to execute bioinformatics applications easily, efficiently, and with good workload balance. Our tests were performed using a real bioinformatics workflow, with fragments generated by the illumina sequencer, having achieved good performance in practice.